Ferromagnetic Materials: Noncentrosymmetric Magnets Hosting Magnetic Skyrmions (Adv. Mater. 25/2017). Issue 25 (3rd July 2017) - Kanazawa, Naoya; Seki, Shinichiro; Tokura, Yoshinori
Abstract : Magnetic skyrmions, i.e., nanometric swirling spin textures with a topologically protected particle nature, are reviewed in article number1603227 by Naoya Kanazawa, Shinichiro Seki, and Yoshinori Tokura. Skyrmions show unique interactions with electric current through the associated emergent electromagnetic fields, and such characters highlight skyrmions as a potential information carrier for high‐density magnetic storage devices with excellent energy efficiency.